(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The doctor’s knowledge of the individual anatomy from the standpoint of the three-dimensional topography of the organ structures of each patient is becoming a leading task on the way to solving the issues of high-quality care provided by modern medical practice. The interactive anatomical atlas of 3D images "Pirogov" allows you to transfer the study of disciplines of anatomical nature to a new mainstream of computational anatomy, or anatomia in silico.